Marketing Strategies in SMEs : A Literature Review on Concepts and New-Age Approaches - Wani, Priyanka; Palkar, Apoorva (AMC Indian Journal of Entrepreneurship, 2023)
Purpose : An in-depth examination of the basic function of marketing strategies as the cornerstone of strategic marketing initiatives is done in this study. Understanding the wide range of marketing techniques used by various company types and industries is essential, given their significance. The field of marketing tactics has changed significantly in the last 20 years, especially when it comes to SMEs. It was also crucial to comprehend how this area has changed over time. Methodology : This study examined the body of research on marketing strategy in the context of small and medium-sized enterprises (SMEs). The study attempted to understand how the dynamics around marketing strategy have evolved by reviewing the research that has been done on the subject over the previous 20 years or more. The study used analytical methods and techniques to examine the literature over the past 20 years via a variety of lenses (themes examined to date). Findings : Marketing strategies and SME performance are linked, as the empirical literature review demonstrated. The literature study was helpful in identifying the main cohorts and subjects that have been the subject of prior research. Digital marketing emerged as the second most popular issue, with marketing strategy appearing to be the theme that garnered the most attention overall. Further research is necessary to understand how this field is changing and what are the important patterns that can be capitalized upon. The data also showed that a lot of work has been done recently in this area. Practical Implications : The study shed light on the ways in which SMEs utilize marketing strategies to enhance their performance. That being said, because the research focuses on FMCG companies, it has limitations in that it did not provide perspectives from other industries. SMEs’ marketing approaches and problems vary depending on the industry in which they operate. Originality : This work sheds light on the comparison of conventional and modern approaches using the lenses of different cohorts that have been investigated thus far, in contrast to previous research on marketing strategies and SMEs.